DNA methylation regulates mouse cardiac myofibril gene expression during heart development. Issue 1 (December 2015) - Xu, Yang; Liu, Lingjuan; Pan, Bo; Zhu, Jing; Nan, Changlong; Huang, Xupei; Tian, Jie
Abstract Background It is well known that epigenetic modifications play an important role in controlling the regulation of gene expression during the development. Our previous studies have demonstrated that the expression of fetal troponin I gene (also called slow skeletal troponin I, ssTnI) is predominated in the fetal stage, reduced after birth and disappeared in the adulthood. The mechanism underlying the developmentally related ssTnI gene regulation is not clear. In this study, we have explored the epigenetic role of DNA methylation in the regulation of ssTnI expression in the heart during the development. Results The DNA methylation levels of CpG island and CpG dinucleotides region were detected using methylation specific PCR (MSP) and bisulfite sequence PCR (BSP) in 2000 bp upstream and 100 bp upstream of ssTnI gene promoter. Real time RT-PCR and Western blot were used to detect ssTnI mRNA and protein expression levels. We found that DNA methylation levels of the CpG dinucleotides region in ssTnI gene promoter were increased with the development, corresponding to a decreased expression of ssTnI gene in mouse heart. However the DNA methylation levels of CpG islands in this gene were not changed during the development. Application of a methylation inhibitor, 5-Azacytidine, in cultured myocardial cells partially prevented the decline of ssTnI expression. Conclusion Our results indicate that DNA methylation, as an epigenetic intervention, plays a role in the regulation of the fetal TnI gene expression in the heat during the development.